Factors influencing platelet clumping during peripheral blood hematopoietic stem cell collection. Issue 5 (1st February 2017) - Mathur, Gagan; Mott, Sarah L.; Collins, Laura; Nelson, Gail A.; Knudson, C. Michael; Schlueter, Annette J.
Abstract : BACKGROUND: Platelet clumping is a common occurrence during peripheral blood hematopoietic stem cell (HSC) collection using the Spectra Optia mononuclear cell (MNC) protocol. If clumping persists, it may prevent continuation of the collection and interfere with proper MNC separation. This study is the first to report the incidence of clumping, identify precollection factors associated with platelet clumping, and describe the degree to which platelet clumping interferes with HSC product yield. STUDY DESIGN AND METHODS: In total, 258 HSC collections performed on 116 patients using the Optia MNC protocol were reviewed. Collections utilized heparin in anticoagulant citrate dextrose to facilitate large‐volume leukapheresis. Linear and logistic regression models were utilized to determine which precollection factors were predictive of platelet clumping and whether clumping was associated with product yield or collection efficiency. RESULTS: Platelet clumping was observed in 63% of collections. Multivariable analysis revealed that a lower white blood cell count was an independent predictor of clumping occurrence. Chemotherapy mobilization and a lower peripheral blood CD34+ cell count were predictors of the degree of clumping. Procedures with clumping had higher collection efficiency but lower blood volume processed on average, resulting in no difference in collection yields. Citrate toxicity did not correlate with clumping. CONCLUSION: Although platelet clumping is a common technical problem seen during HSC collection, the total CD34+ cell‐collection yields were not affected by clumping. WBC count, mobilization approach, and peripheral blood CD34+ cell count can help predict clumping and potentially drive interventions to proactively manage clumping.